Internet connectivity disruption in United Kingdom (United Kingdom) - Voidly (2026)
CRITICAL severity disruption detected in United Kingdom. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: GB-2026-0013
Keywords: internet disruption; GB; disruption; critical